2012
DOI: 10.1111/hiv.12000
|View full text |Cite
|
Sign up to set email alerts
|

Metformin: a cheap and well‐tolerated drug that provides benefits for viral infections

Abstract: ObjectivesInsulin resistance in viral infections is common. We have explored the effectiveness of metformin for alleviating insulin resistance in HIV-infected patients and assessed the relevance of the ataxia-telangiectasia mutated (ATM) rs11212617 variant in the clinical response with the rationale that metformin modulates cellular bioenergetics in an ATM-dependent process. MethodsHIV-infected patients (n = 385) were compared with controls recruited from the general population (n = 300) with respect to the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…While an association between metformin and improved immune reconstitution has not been previously described, there is data from HIV-uninfected patients demonstrating that metformin exerts anti-inflammatory properties, beyond its glucose properties. Metformin inhibits release of cytokines, such as interleukin-6 and interleukin-8, from coronary artery vasculature [6]. Whether this anti-inflammatory effect is at work to enhance immune recovery in HIV-infected patients is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…While an association between metformin and improved immune reconstitution has not been previously described, there is data from HIV-uninfected patients demonstrating that metformin exerts anti-inflammatory properties, beyond its glucose properties. Metformin inhibits release of cytokines, such as interleukin-6 and interleukin-8, from coronary artery vasculature [6]. Whether this anti-inflammatory effect is at work to enhance immune recovery in HIV-infected patients is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…The use of metformin, an AMPK activator used extensively to treat type 2 diabetes, has been indicated for other metabolic conditions based on the rationale that insulin-sensitising agents might be effective [106], and the mode of action of metformin has guided our own experiments on cancer, aging, and viral infection [65, 107, 108]. We have shown that the beneficial effects of this biguanide class drug, which was initially obtained from Galega officinalis , are universal in patients with metabolic complications and negligible in patients without such complications.…”
Section: Metformin And/or Rapamycin and Plant-derived Polyphenols:mentioning
confidence: 99%
“…More important, an observational study from the UK in more than 78,000 subjects reported that type 2 diabetes patients treated with metformin had improved survival, as compared to those not receiving metformin, as well as matched, non-diabetic patients (Bannister and others 2014). Consistent with these putative effects on survival, accumulating observational and pre-clinical data have revealed benefits of metformin use that extend far beyond type 2 diabetes, and include protection against cardiovascular disease (Forouzandeh and others 2014), dyslipidemias in mice (Geerling and others 2014), certain cancers (Morales and Morris 2015; Sehdev and others 2015) infections (Joven and others 2013) and frailty syndrome (Sumantri and others 2014). Further, while metformin was shown to have no effect on bone mass and fracture healing time in young rodents (Jeyabalan and others 2013) or surgical stress in humans (Duncan and others 2007), it was found to reduce prolonged tracheal intubation and overall morbidities following surgery (Duncan and others 2007).…”
Section: Pharmacologic Strategiesmentioning
confidence: 95%